2016
DOI: 10.1681/asn.2015091029
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Renal Disease in Bardet–Biedl Syndrome

Abstract: Bardet-Biedl syndrome is a rare autosomal recessive, multisystem disease characterized by retinal dystrophy, renal malformation, obesity, intellectual disability, polydactyly, and hypogonadism. Nineteen disease-causing genes () have been identified, of which mutations in are most common in North America and Europe. A hallmark of the disease, renal malformation is heterogeneous and is a cause of morbidity and mortality through the development of CKD. We studied the prevalence and severity of CKD in 350 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(130 citation statements)
references
References 16 publications
8
118
0
4
Order By: Relevance
“…In the recent publication on the English cohort, it has been demonstrated that mutations in BBS2, 10 and 12 correlated with a most severe renal dysfunction compared with BBS1 , confirming previous findings [4]. In addition, the study pointed that truncating mutations compared with missense mutations were associated with kidney dysfunction, suggesting that any BBS gene when strongly affected may lead to kidney disease.…”
Section: Evidence Supporting the Role Of Local Bbs Dysfunction In Thesupporting
confidence: 82%
See 2 more Smart Citations
“…In the recent publication on the English cohort, it has been demonstrated that mutations in BBS2, 10 and 12 correlated with a most severe renal dysfunction compared with BBS1 , confirming previous findings [4]. In addition, the study pointed that truncating mutations compared with missense mutations were associated with kidney dysfunction, suggesting that any BBS gene when strongly affected may lead to kidney disease.…”
Section: Evidence Supporting the Role Of Local Bbs Dysfunction In Thesupporting
confidence: 82%
“…The majority of reports show that more than half of the BBS patients exhibit normal eGFR [11, 12]. A recent retrospective study on a total of 350 BBS patients from the United Kingdom showed that the prevalence of CKD stage II-V were 42% and 31% in adult and children respectively and no difference between genders have been reported [4]. Patients with normal glomerular filtration rate (GFR) included either subjects with structural renal abnormalities and individuals with no any significant anomalies on kidney ultrasound.…”
Section: Renal Abnormalities In Bbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports showed that BBS1 mutations are associated with a less severe phenotype compared with other BBS genes [19] , especially BBS10 [20,21] . However, in a recent study, it was demonstrated that biallelic truncating mutations in any gene correlated with more severe renal disease compared with missense mutations, suggesting that any BBS gene, when strongly affected, may result in severe kidney dysfunction [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome has a genetic origin, and to date 21 genes have been associated with human BBS but it is presumable that other unknown genes are yet to be discovered [1]. Even though many efforts have been devoted to address genotype-phenotype correlation, there is still little information on this issue [2-4]. …”
Section: Introductionmentioning
confidence: 99%